PENGARUH POC LIMBAH TAHU TERHADAP PERTUMBUHAN BIBIT TEBU (Saccharum officinarum L.) SINGLE BUD CHIPS - Kolnel, Yusi; Nurhayati, Nurhayati; Sopiana, Sopiana; Rosmalinda, Rosmalinda (Politeknik Negeri Ketapang, 2024)
Sugarcane (Saccharum ofcinarum L.) is the main crop as sugar-producing crop. Continuous use of inorganic fertilizers can cause environmental damage. Tofu liquid waste contains some nutrients and can used as liquid organic fertilizer for example protein 40-60%, carbohydrate 25-50% and fat 10%. This study aims to determine the effect of tofu waste liquid as liquid organic fertilizer on sugarcane seed by single bud chips . This research was conducted at the Ketapang State Polytechnic, Dalong, using a Completely Randomized Design (CRD), which consisted of 5 treatments with 5 replications, with a concentration of L0 = 0. %, L1 = 100%, L2 = 150%, L3 = 200% and L4 = 250%. Observation parameters include plant height (cm), stem diameter (mm), number of leaves (strands), and leaf length (cm). The results showed that the application tofu liquid waste fertilizer had a significant effect on the growth of sugarcane single bud chips on the parameters of plant height, stem diameter, number of leaves and leaf length The best treatment was L1 dose (100 mL/polybag of tofu liquid waste) to increase the growth of sugarcane seed by single bud chips.